2016
DOI: 10.1016/j.ijscr.2016.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Psoas muscle abscess simulating acute appendicits: A case report

Abstract: HighlightsPsoas muscle is an powerful thigh flexor.Psoas muscle abscess is a rare clinical entity with a high mortality rate.We report a case of psoas abscess presenting with symptoms of acute appendicitis.Surgical drainage and antibiotic therapy was conducted.Patient was released 7 days after treatment with no complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 11 publications
0
9
0
3
Order By: Relevance
“…[5][6][7]9,11,13 CT is the imaging mode of choice for IPA detection. [4][5][6]9,11,16 In Tabrizian et al, 89% (54 of 61) of patients were diagnosed by CT. 6 Wong et al, reported that, in 95% (40/42) of all cases, IPAs were diagnosed via CT. 9 Taiwo et al, considered CT to be the diagnostic mode of choice; the sensitivity approached 100%, consistent with our findings . 16 Mueller et al, were the first to use PCD to treat an IPA, in 1984.…”
mentioning
confidence: 99%
“…[5][6][7]9,11,13 CT is the imaging mode of choice for IPA detection. [4][5][6]9,11,16 In Tabrizian et al, 89% (54 of 61) of patients were diagnosed by CT. 6 Wong et al, reported that, in 95% (40/42) of all cases, IPAs were diagnosed via CT. 9 Taiwo et al, considered CT to be the diagnostic mode of choice; the sensitivity approached 100%, consistent with our findings . 16 Mueller et al, were the first to use PCD to treat an IPA, in 1984.…”
mentioning
confidence: 99%
“…Akut apandisit, divertikülit, Crohn hastalığı, kolorektal karsinom ve rektal travma gibi bazı durumlar sekonder iliopsoas absesine neden olabilir (6). Günümüzde primer iliopsoas absesi ise özellikle immün yetmezliği (AIDS, alkolikler), Diabetes Mellitus, ileri yaşlı, Pott hastalığı olan hastalarda teşhis edilmektedir ve en sık görülen ana patojen etken Staphylococcus aureus' dur (7,8). Primer iliopsoas apsesi hastalarında uygun tedavi ile daha iyi prognoz göstermekle beraber mortalite %2,5-18,9 civarında bildirilmiştir (8).…”
Section: Discussionunclassified
“…Günümüzde primer iliopsoas absesi ise özellikle immün yetmezliği (AIDS, alkolikler), Diabetes Mellitus, ileri yaşlı, Pott hastalığı olan hastalarda teşhis edilmektedir ve en sık görülen ana patojen etken Staphylococcus aureus' dur (7,8). Primer iliopsoas apsesi hastalarında uygun tedavi ile daha iyi prognoz göstermekle beraber mortalite %2,5-18,9 civarında bildirilmiştir (8). İliopsoas apselerinin gastrointestinal sistemden kaynaklı etyolojik nedenleri arasında 1. sırada Crohn hastalığı (%60) 2. sırada ise apandisit (%16) gelir (2).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…There is usually associated leucocytosis and an ultrasound may show fluid collection in the right iliac fossa. 9 An appendicular mass is most commonly associated with acute inflammation, however a small percentage may also be malignant. 10 There are two distinct types of AA, obstructive and catarrhal.…”
Section: Discussionmentioning
confidence: 99%